2009
DOI: 10.1159/000252836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Gabapentin on Postoperative Nausea and Vomiting after Open Cholecystectomy: A Prospective Randomized Double-Blind Placebo-Controlled Study

Abstract: Objective: To evaluate the effect of gabapentin on the incidence and severity of postoperative nausea and vomiting (PONV) after open cholecystectomy. Subjects and Methods: A total of 90 patients scheduled for elective open cholecystectomy were randomly assigned to either a gabapentin group (600 mg, 2 h before surgery) or a placebo group. For the analysis, 1 patient was excluded from the gabapentin group and 2 patients from the placebo group. A standard technique was used for anesthesia. Pethidine and metoclopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…A similar study in patients undergoing open cholecystectomy found a dose of 600 mg of oral gabapentin to be effective in reducing the incidence but not the severity of PONV. 27 The precise mechanism of antiemetic action of gabapentin remains speculative. It has been proposed that the drug may exert its action by virtue of tachykinin (NK-1) receptor antagonism and mitigation of tachykinin neurotransmitter (substance P) activity, which has been implicated in emetogensis.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in patients undergoing open cholecystectomy found a dose of 600 mg of oral gabapentin to be effective in reducing the incidence but not the severity of PONV. 27 The precise mechanism of antiemetic action of gabapentin remains speculative. It has been proposed that the drug may exert its action by virtue of tachykinin (NK-1) receptor antagonism and mitigation of tachykinin neurotransmitter (substance P) activity, which has been implicated in emetogensis.…”
Section: Discussionmentioning
confidence: 99%
“…Eight trials were classified as overall low risk of bias, [39, 43, 46, 56, 59, 72, 73, 85] 18 trials were overall unclear risk of bias [21, 23, 24, 26, 28, 29, 31, 36, 38, 42, 52, 54, 55, 61, 65, 66, 68, 69, 80] and 48 trials were classified as high risk of bias, [20, 22, 25, 27, 30, 3235, 37, 40, 41, 44, 45, 4751, 53, 57, 58, 60, 62–64, 67, 70, 71, 7479, 81–84, 86–94] (Fig. 2: Bias assessment).…”
Section: Resultsmentioning
confidence: 99%
“…[20, 22–24, 2832, 34–37, 41, 43, 45, 4751, 53, 5557, 6164, 6771, 75, 77–79, 81, 82, 8590, 92, 94] In 30 trials, gabapentin was administered in combination with a basic, non-opioid/opioid analgesic regimen [20, 22, 23, 26, 28, 3032, 37–41, 43, 46, 49, 54, 56, 57, 59, 61, 72, 73, 76, 79, 80, 82, 87, 90, 91]. In 44 trials, gabapentin was administered together with an opioid as the only analgesic [20, 25, 27, 29, 3336, 44, 45, 47, 48, 50–53, 55, 58, 62–71, 74, 75, 77, 78, 83–86, 88, 89, 92–94].…”
Section: Resultsmentioning
confidence: 99%
“…Ketamine was used intraoperatively, which can reduce post-operative cholecystectomy pain and continue to work as an adjuvant up to 24 hours after administration to reduce pain scores and opioid use [4]. Similarly, gabapentin and pregabalin have been shown to decrease post-operative pain and narcotic consumption requirements, which also reduces post-operative nausea and vomiting and associated mechanical pain [5,6].…”
Section: Discussionmentioning
confidence: 99%